Introduction to acoustics - Finch, Robert D. (Pearson, 2005)
Focusing on the systems and engineering aspects of acoustics, this text emphasizes the importance of speech and hearing in our lives. It offers real-world applications while combining principles from both electrical and mechanical engineering, along with instrumentation and basic measurement techniques.